The Lama Question : Violence, Sovereignty, and Exception in Early Socialist Mongolia - Kaplonski, C. (Christopher) (Book collections on Project MUSE., 2014)
Before becoming the second socialist country in the world in 1921, Mongolia had been a Buddhist feudal theocracy. Combatting the influence of the dominant Buddhist establishment to win the hearts and minds of the Mongolian people was one of the most important challenges faced by the new socialist government. Chris Kaplonski examines this critical, violent time in the development of Mongolia as a nation-state and its ongoing struggle for independence and recognition.